3-Phenyllactic acid production by Lactobacillus crustorum strains isolated from naturally fermented vegetables. (September 2021) - Xu, Juan-Juan; Sun, Jin-Zhi; Si, Kuo-Lin; Guo, Chun-Feng
Abstract: 3-Phenyllactic acid (3-PLA) is a bioactive compound with broad-spectrum antibacterial and antifungal activity and several desirable pharmacological properties. In this study, 351 lactic acid bacterial strains isolated from naturally fermented Chinese vegetable samples were analyzed for their 3-PLA-producing ability, and three strains showing the greatest 3-PLA-producing ability were selected for further optimizing the fermentation conditions to enhance their 3-PLA yields. The results showed that all the strains were able to produce 3-PLA in MRS broth, but there were considerable variations in their 3-PLA-producing ability among the strains and among the species. Lactobacillus crustorum showed significantly higher 3-PLA-producing ability than the other species. In particular, L. crustorum NWAFU 1078 produced up to 45.2 mmol/L 3-PLA with a 73% substrate conversion rate under the optimized fermentation conditions that the culture was inoculated into MRS broth supplemented with 60 mmol/L phenylpyruvic acid as a substrate, 5.0% CaCO3 as a neutralizer and incubated for 48 h at 30 °C. This study indicates the possibility of the biotransformation of phenylpyruvic acid by L. crustorum NWAFU 1078 for highly efficient 3-PLA production. Highlights: Lactic acid bacilli produced more 3-phenyllactic acid (3-PLA) than lactic acid cocci. L. crustorum species produced highest 3-PLA among the 12 species of lactobacilli. L. crustorum NWAFU 1078 produced 45.2 mmol/L 3-PLA under the optimal conditions. L. crustorum genome harbors 3 L- and 3 D-lactate dehydrogenase genes.